Peran Produktif Wanita Pesisir dalam Pengolahan Hakau Udang Desa Pahlawan Tanjung Tiram - Uswatun Hasanah Hasanah; Wahyu Indah Sari; Annisa Ilmi Faried (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this community service is to empower coastal women in the field of shrimp-based processing, as well as increase the income of coastal women during the pandemic through shrimp processing. The solution of the partner problem by making a presentation first about increasing fishermen's income through processing marine products, then explaining the manufacture of hakau hudang by providing recipes and ways of processing shrimp into shrimp hakau, conducting discussions about the materials delivered, as well as evaluating the results of empowering coastal women in the field of shrimp-based processing so as to increase the income of coastal women during the pandemic through shrimp processing. The result of this activity is that diversification of shrimp processing is a very effective way to increase community income in Desa Pahlawan, devotion is also achieved and successfully by providing information to the mothers of Hero Village in managing marine products